Do traditional and reverse swimming training periodizations lead to similar aerobic performance improvements? - Clemente-Suarez, V. J.; Fernandes, R. J.; de Jesus, K.; Pelarigo, J. G.; Arroyo-Toledo, J. J.; Vilas-Boas, J. P. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of the present research was to analyze the modifications on aerobic swimming performance indicators after performing traditional and reverse training periodizations (TTP and RTP, respectively). METHODS: Seventeen trained swimmers were divided into two groups: one group (N.=7) performed 10 weeks of TTP (based on high volumes and an increased intensity during the program) and the second one (N.=10) was involved in a similar period of RTP (based on low volumes and high intensity during the entire program). Velocity (v), heart rate (HR) and rate of perceived exertion (RPE) at the intensity of 4 mmol/L of blood lactate concentration, v, HR, RPE, stroke rate, stroke length and stroke index at the minimal intensity that elicits maximal oxygen uptake (vVO2max) and maximal oxygen uptake (VO2max) were analyzed pre- and post-training intervention. RESULTS: Stroke index significantly increased (2.9±0.3 vs. 3.1±0.2; P<0.05) and stroke rate and RPE at vVO2max significantly decreased after performing TTP. In the RTP group, VO2max significantly increased (50.9±6.6 vs. 54.1±4.7 mL/min/kg). CONCLUSIONS: In conclusion, RTP performed for 10 weeks was more effective than TTP to increase the VO2max in trained swimmers, but TTP yields a higher swimming efficiency, probably due to the higher volume of technical training performed during the training program.